A kind of anti-fouling self-cleaning elastic nylon and preparation method thereof
By introducing a long chain structure of fluorine carbon into the nylon structure and using melt copolymerization to prepare elastic nylon that is resistant to stains and not easy to clean, the problem of existing nylon materials being easily stained and difficult to clean, and the long-lasting anti-fouling performance and environmental protection of the material are achieved.
Patent Information
- Application Number
- CN202410067658.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-17
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-01-17
AI Technical Summary
Existing elastic nylon materials are easy to contaminate and not easy to clean. Traditional anti-fouling treatment methods have problems of damage and loss of anti-fouling coatings, and cause pollution to the environment.
By introducing a long chain structure of fluorine carbon as a hydrophobic chain segment in the nylon structure, melt copolymerization is used to prepare an elastic nylon that is anti-fouling self-cleaning, and the ratio of soft and hard segments is regulated to improve the antifouling performance and durability of the material.
The anti-fouling self-cleaning effect of nylon materials is achieved, and the damage and loss of anti-fouling coating is avoided, and the environment will not be polluted. The material has excellent toughness, elasticity and easy decontamination.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon, in particular to anti-fouling self-cleaning elastic nylon and a preparation method thereof. Background Art
[0002] Nylon is used in many fields such as clothing, decoration, and industry due to its excellent mechanical properties and wear resistance. Elastic nylon is usually prepared by copolymerization of long carbon chain nylon, polyether or polyester chain segments. These long chain structures are used as soft segments to give it excellent elasticity, cold resistance and temperature resistance. It is widely used in sports products, medical equipment, aerospace and other fields. During use, elastic nylon products have improved water absorption due to the introduction of long carbon chain structures, making them more easily combined with various water-soluble stains and sweat, and difficult to clean. With the improvement of people's living standards and the enhancement of health awareness, people have put forward higher requirements for the cleanliness of these products. Therefore, there is an urgent need for anti-fouling and self-cleaning elastic nylon.
[0003] Traditional anti-fouling products are often prepared by post-finishing or surface coating. For example, Chinese invention patent publication number CN110952304A discloses an antibacterial and easy-to-remove finishing process for nylon fabrics. The process steps include: (1) pre-treating the fabric to obtain a semi-finished product, (2) placing the semi-finished product into a prepared finishing liquid for functional finishing by immersion, (3) pre-baking the finished fabric at 110-130°C for 30-60s and baking at 150-180°C for 45-60s, and (4) rolling up the baked fabric after natural cooling. The present invention performs antibacterial treatment on the nylon fabric while performing easy-to-remove finishing, thereby improving the antibacterial property and easy-to-remove property of the nylon fabric. However, the surface anti-fouling coating of the anti-fouling nylon is very likely to be damaged and lost during use or washing, and its anti-fouling performance will decrease or even be lost. In addition, the anti-fouling agent will enter the natural environment with the washing water, causing serious pollution problems. For example, perfluorooctane sulfonic acid substances used for anti-fouling treatment in the textile industry have been banned in many countries. Therefore, it is extremely urgent to prepare efficient, durable, anti-fouling, easy-to-clean elastic nylon materials. Summary of the invention
[0004] In order to solve the problem that elastic nylon is easy to be contaminated and difficult to clean in the prior art, the present invention provides an anti-fouling self-cleaning elastic nylon and a preparation method thereof. The elastic nylon adopts a fluorocarbon long chain structure as a soft segment, and adopts melt copolymerization to prepare the anti-fouling self-cleaning elastic nylon. By introducing this flexible hydrophobic segment into the nylon structure, it can be ensured that the material has excellent elasticity while giving it a certain ability to reduce the binding of stains, thereby giving it a certain anti-fouling self-cleaning effect. In addition, the introduction of modified anti-fouling substances by copolymerization can effectively avoid the problems of breakage and loss during later use, and will not cause any pollution problems to the environment.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] In the first aspect, the present invention provides a method for preparing anti-fouling self-cleaning elastic nylon, comprising the following steps: randomly copolymerizing a soft segment monomer and a hard segment monomer to obtain an anti-fouling self-cleaning elastic nylon; the raw materials of the soft segment monomer are a diamine containing a fluorocarbon structure and an alkane dibasic acid, or a dibasic acid containing a fluorocarbon structure and an alkane diamine; the raw materials of the hard segment monomer are lactam, or an alkane dibasic acid and an alkane diamine.
[0007] The present invention introduces a hydrophobic fluorocarbon segment into a nylon polyamide segment, and by regulating the ratio of the hydrophobic fluorocarbon segment, the binding ability of stains is reduced, so that the nylon has anti-fouling self-cleaning properties, and the anti-fouling properties of the nylon can be made more durable through copolymerization, which can effectively avoid the problems of breakage and loss during later use. In addition, the anti-fouling nylon in the present invention still has strong toughness and elasticity, the introduced fluorocarbon structure segment and alkane dibasic acid are flexible segments, and the original nylon polyamide segment is a hard segment. Through the random copolymerization of the soft segment and the hard segment, the ratio of softness and hardness is controlled, so that the copolymerized nylon has good toughness and elasticity while having good anti-fouling properties, thereby improving product performance and expanding the scope of application.
[0008] Preferably, x:y is the mass ratio of the hard segment monomer to the soft segment monomer in the anti-fouling self-cleaning elastic nylon, x:y = 0.4-0.9: 0.1-0.6, x + y = 1. More preferably, x:y = 0.5-0.65: 0.35-0.5, x + y = 1
[0009] Preferably, the structural formula of the diamine containing a carbon fluorine structure is: Here, n is an integer from 6 to 20.
[0010] Preferably, the structural formula of the dibasic acid containing a carbon fluorine structure is: Here, n is an integer from 6 to 20.
[0011] Preferably, the lactam is at least one of caprolactam, decanolactam, undecanolactam and laurolactam.
[0012] Preferably, the alkane dibasic acid is one of adipic acid, glutaric acid and sebacic acid.
[0013] Preferably, the alkane diamine is one of hexamethylenediamine, pentamethylenediamine and decamethylenediamine.
[0014] Preferably, the structural formula of the soft segment monomer is as follows:
[0015] Preferably, when the raw materials of the hard segment monomer are alkane dibasic acid and alkane diamine, the structural formula of the anti-fouling self-cleaning elastic nylon is as follows:
[0016] Preferably, the method comprises the following steps: mixing the raw materials of the soft segment monomer and the hard segment monomer to ensure that the acid-amine molar ratio is 1:1 to 1.1, adding a catalyst and desalted water to carry out a salt-forming reaction, and then sequentially carrying out a prepolymerization reaction and a polymerization reaction to obtain a stain-resistant self-cleaning elastic nylon.
[0017] Preferably, the salt-forming reaction is: salt-forming at 60-80° C. under normal pressure for 1-2 hours.
[0018] Preferably, the prepolymerization reaction is: prepolymerization at 220-260° C. for 1-2 hours, and a reaction pressure of 1.0-2.0 MPa.
[0019] Preferably, the polymerization reaction is: slowly draining water and releasing the pressure to normal pressure at 220-260° C. for 0.5-2 h, and evacuating to -0.01-0.1 MPa for 0.5-3 h.
[0020] In a second aspect, the present invention also provides an anti-fouling self-cleaning elastic nylon prepared by the above preparation method.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) By introducing a fluorocarbon long chain structure into the nylon structure as a hydrophobic segment, nylon is given a certain ability to reduce the binding of stains, thereby giving it a certain anti-fouling self-cleaning effect;
[0023] (2) Introducing modified antifouling substances by copolymerization can effectively avoid damage and loss during later use, and will not cause any pollution to the environment;
[0024] (3) By adjusting the ratio of soft and hard segments, nylon can have excellent toughness and elasticity while also having excellent anti-fouling and self-cleaning effects. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0026] The preparation of anti-fouling self-cleaning elastic nylon includes the following steps:
[0027] Mix diamines containing fluorocarbon structure, alkane dibasic acid, alkane diamines or dibasic acid containing fluorocarbon structure, alkane diamines, alkane dibasic acid or diamine containing fluorocarbon structure, alkane diamines, lactam or dibasic acid containing fluorocarbon structure, alkane diamines, lactam, and ensure that the acid-amine molar ratio is 1:1-1.1; then, add catalyst and deionized water to form salt at 60-80°C under normal pressure for 1-2 hours, prepolymerize at 220-260°C for 1-2 hours, reaction pressure is 1.0-2.0MPa, slowly drain and release pressure to normal pressure at 220-260°C, react for 0.5-2 hours, evacuate to -0.01-0.1MPa, react for 0.5-3 hours, and obtain anti-fouling self-cleaning elastic nylon. x:y is the mass ratio of the hard segment monomer to the soft segment monomer in the anti-fouling self-cleaning elastic nylon, x:y=0.4-0.9:0.1-0.6, x+y=1.
[0028] The structural formula of diamine containing carbon fluorine structure is: Wherein, n is an integer of 6 to 20. The structural formula of the soft segment monomer is:
[0029] The structural formula of the dibasic acid containing carbon fluoride structure is: Wherein, n is an integer of 6 to 20. The structural formula of the soft segment monomer is:
[0030] The lactam is at least one of caprolactam, decanedioic acid, undecanoic acid and dodecanoic acid. The alkane dibasic acid is one of adipic acid, glutaric acid and sebacic acid. The alkane diamine is one of hexamethylenediamine, pentamethylenediamine and decanedioamine.
[0031] Example 1
[0032] Weigh 1360g of caprolactam, 146g of adipic acid, 800g of perfluorohexadecanediamine and 2g of sodium phosphite into the reactor, add 500mL of deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80℃ for 1h, heat to 240℃, keep the pressure in the reactor at 1.5MPa, react for 1h, gradually release the pressure to normal pressure, heat to 260℃ simultaneously, react for 1h, evacuate to -0.03MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the material and pelletize it to obtain anti-fouling self-cleaning elastic nylon chips (mass ratio of hard segment monomer to soft segment monomer x:y=0.59:0.41).
[0033] Example 2
[0034] Weigh 1380g of lauryl lactam, 146g of adipic acid, 800g of perfluorohexadecane diamine and 2g of sodium phosphite into a reactor, add 500mL of deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80°C for 1h, heat to 270°C, keep the pressure in the reactor at 1.5MPa, react for 1h, gradually release the pressure to normal pressure, keep the temperature at 270°C, react for 1h, evacuate to -0.03MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the material and pelletize it to obtain anti-fouling self-cleaning elastic nylon slices (mass ratio of hard segment monomer to soft segment monomer x:y=0.59:0.41).
[0035] Example 3
[0036] Weigh 1360g of caprolactam, 105g of pentamethylenediamine, 860g of perfluorohexadecane diacid and 2g of sodium phosphite and add them to the reactor, then add 500mL of deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80°C for 1h, heat to 240°C, keep the pressure in the reactor at 1.5MPa, react for 1h, gradually release the pressure to normal pressure, heat to 260°C simultaneously, react for 1h, evacuate to -0.03MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the material and pelletize it to obtain anti-fouling self-cleaning elastic nylon slices (mass ratio of hard segment monomer to soft segment monomer x:y=0.61:0.39).
[0037] Example 4
[0038] Weigh 1380g of lauryl lactam, 105g of pentamethylenediamine, 860g of perfluorohexadecane diacid and 2g of sodium phosphite and add them to the reactor, then add 500mL of deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80°C for 1h, heat to 270°C, keep the pressure in the reactor at 1.5MPa, react for 1h, gradually release the pressure to normal pressure, keep the temperature at 270°C, react for 1h, evacuate to -0.03MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the material and pelletize it to obtain anti-fouling self-cleaning elastic nylon slices (mass ratio of hard segment monomer to soft segment monomer x:y=0.62:0.38).
[0039] Example 5
[0040] Weigh 465g hexamethylenediamine, 730g adipic acid, 800g perfluorohexadecanediamine and 2g sodium phosphite into a reactor, add 800mL deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80°C for 1h, heat to 230°C, keep the pressure in the reactor at 1.5MPa, react for 1h to generate prepolymer, gradually release the pressure to normal pressure, keep the temperature at 260°C, react for 1h, evacuate to -0.05MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the material and pelletize it to obtain anti-fouling self-cleaning elastic nylon chips (mass ratio of hard segment monomer to soft segment monomer x:y=0.53:0.47).
[0041] Example 6
[0042] Weigh 730g of adipic acid, 700g of hexamethylenediamine, 860g of perfluorohexadecane diacid and 2g of sodium phosphite into a reactor, add 800mL of deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80°C for 1h, heat to 230°C, keep the pressure in the reactor at 1.5MPa, react for 1h to generate a prepolymer, gradually release the pressure to normal pressure, keep the temperature at 260°C, react for 1h, evacuate to -0.05MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the material and pelletize it to obtain anti-fouling self-cleaning elastic nylon chips (mass ratio of hard segment monomer to soft segment monomer x:y=0.57:0.43).
[0043] Example 7
[0044] Weigh 1360g of caprolactam, 73g of adipic acid, 400g of perfluorohexadecanediamine and 2g of sodium phosphite into the reactor, add 500mL of deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80℃ for 1h, heat to 240℃, keep the pressure in the reactor at 1.5MPa, react for 1h, gradually release the pressure to normal pressure, heat to 260℃ simultaneously, react for 1h, evacuate to -0.03MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the material and pelletize it to obtain anti-fouling self-cleaning elastic nylon chips (mass ratio of hard segment monomer to soft segment monomer x:y = 0.75:0.25).
[0045] Example 8
[0046] Weigh 1360g of caprolactam, 36g of adipic acid, 200g of perfluorohexadecanediamine and 2g of sodium phosphite into the reactor, add 500mL of deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80℃ for 1h, heat to 240℃, keep the pressure in the reactor at 1.5MPa, react for 1h, gradually release the pressure to normal pressure, heat to 260℃ simultaneously, react for 1h, evacuate to -0.03MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the material and pelletize it to obtain anti-fouling self-cleaning elastic nylon chips (mass ratio of hard segment monomer to soft segment monomer x:y=0.85:0.15).
[0047] Comparative Example 1
[0048] Weigh 1600g of adipic acid, 1160g of hexamethylenediamine, 900g of polyetheramine (Mn~900) and 3.5g of sodium phosphite and add them to the reactor, then add 800mL of deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80℃ for 1h, heat to 220℃, keep the pressure in the reactor at 1.5MPa, react for 1h to generate prepolymer, gradually release the pressure to normal pressure, keep the temperature at 260℃, react for 1h, evacuate to -0.10MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the discharged material and pelletize it to obtain nylon chips.
[0049] Comparative Example 2
[0050] Weigh 1600g adipic acid, 1160g hexamethylenediamine, 1000g PTMG (Mn~1000) and 3.5g sodium phosphite into the reactor, then add 800mL deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80℃ for 1h, heat to 220℃, keep the pressure in the reactor at 1.5MPa, react for 1h to generate prepolymer, gradually release the pressure to normal pressure, keep the temperature at 260℃, react for 1h, evacuate to -0.50MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the discharged material and pelletize it to obtain nylon chips.
[0051] Comparative Example 3
[0052] The difference from Example 1 is that the mass ratio of the hard segment monomer to the soft segment monomer is x:y=0.3:0.7.
[0053] Weigh 400g of caprolactam, 146g of adipic acid, 800g of perfluorohexadecanediamine and 2g of sodium phosphite into a reactor, add 500mL of deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80°C for 1h, heat to 240°C, keep the pressure in the reactor at 1.5MPa, react for 1h, gradually release the pressure to normal pressure, heat to 260°C simultaneously, react for 1h, evacuate to -0.03MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the discharged material and pelletize to obtain nylon chips.
[0054] Comparative Example 4
[0055] The difference from Example 1 is that the mass ratio of the hard segment monomer to the soft segment monomer is x:y=0.95:0.05.
[0056] Weigh 1700g of caprolactam, 14.6g of adipic acid, 80g of perfluorohexadecanediamine and 2g of sodium phosphite into the reactor, add 500mL of deionized water, start stirring, replace the air in the reactor with nitrogen, stir at 80°C for 1h, heat to 240°C, keep the pressure in the reactor at 1.5MPa, react for 1h, gradually release the pressure to normal pressure, heat to 260°C simultaneously, react for 1h, evacuate to -0.03MPa, and react for 2h. After the reaction is completed, fill with nitrogen to restore to normal pressure, cool the material and pelletize to obtain nylon chips.
[0057] Comparative Example 5
[0058] The difference from Example 1 is that no adipic acid is added.
[0059] Weigh 1360g of caprolactam, 800g of perfluorohexadecanediamine and 2g of sodium phosphite into the reactor, then add 500mL of desalted water, start stirring, replace the air in the reactor with nitrogen, stir at 80℃ for 1h, heat to 240℃, maintain the pressure in the reactor at 1.5MPa, react for 1h, gradually release the pressure to normal pressure, simultaneously heat to 260℃, react for 1h, evacuate to -0.03MPa, and react for 2h.
[0060] The nylon chips prepared in the above examples and comparative examples were melt-spun into 70D / 24f FDY fibers, which were then woven into garters for stain resistance testing. In addition, the garters woven in comparative examples 1 and 2 were treated with surface fluorine-based stain resistance agents ( CB06C6) treatment, followed by padding and drying for stain resistance test. The tensile mechanical properties of the material were tested using a universal testing machine according to the method described in GB / T1040.2-2022; the stain resistance test was evaluated using the method described in FZ / T01118-2012 "Testing and Evaluation of Anti-Stain Performance of Textiles - Decontamination Ease".
[0061] Table 1
[0062]
[0063] Examples 1-8 all use elastic nylon materials prepared by copolymerization modification of the monomers described in the present invention. By introducing a certain amount of hydrophobic functional soft segment structure, the tensile properties of the material are significantly improved, which can ensure that the nylon has excellent toughness and elasticity, and the ability to bind to stains is significantly reduced, thereby giving it excellent stain removal properties and excellent anti-fouling self-cleaning effects. The introduction of modified anti-fouling substances by copolymerization can effectively avoid damage and loss during later use. The stain removal of the material is not limited by the number of washings and will not cause any pollution to the environment.
[0064] When lactam is used as the hard segment raw material, the comparison between Example 1 and Example 2, and Example 3 and Example 4 shows that the segment length of lactam has little effect on the performance of nylon, while Example 1, Example 3, Example 7 and Example 8 show that the higher the hard segment mass ratio in nylon, the worse the mechanical properties of the nylon material will be, and the anti-fouling performance will also be affected due to the decrease in the soft segment ratio, but within the scope of the present invention, the obtained nylon can still obtain good elasticity and anti-fouling performance. When diamine and dibasic acid are used as hard segment raw materials, Examples 5 and 6 show that compared with lactam as the hard segment raw material, the mechanical properties of the obtained nylon will be reduced to a certain extent, but it can still maintain good elasticity and anti-fouling performance.
[0065] Comparative Examples 1 and 2 use conventional soft segments for polymerization experiments, Comparative Example 1 uses polyetheramine as the soft segment, and Comparative Example 2 uses PTMG as the soft segment. The nylon materials prepared in Comparative Examples 1 and 2 do not have easy decontamination properties. Afterwards, the nylon slices prepared in Comparative Examples 1 and 2 are melt-spun into 70D / 24f FDY fibers, which are then woven into garters. The garters are treated with surface fluorine-based antifouling agents, and then subjected to padding and drying treatments for antifouling tests. Although the fluorine-based antifouling agents can temporarily make the garters have a certain degree of easy decontamination properties, as the number of washings increases, the surface antifouling agents are lost, and the antifouling properties of the materials are significantly reduced. At the same time, the washing process will also cause pollution to the environment.
[0066] The ratio of the hard segment to the soft segment in Comparative Example 3 exceeds the specified range of the present invention, and the soft segment content used is too high, resulting in the nylon material becoming sticky after polymerization, making it impossible to carry out pelletizing production, and thus, unable to obtain a nylon finished product.
[0067] The ratio of the hard segment to the soft segment in Comparative Example 4 exceeds the range specified in the present invention. When the soft segment content is too low, the nylon material does not have good stain removal properties, and its mechanical properties also deteriorate, and it does not have excellent elastic properties.
[0068] In Comparative Example 5, when the diamine / acid in the corresponding proportion was not added according to the soft segment content, polymerization could not be achieved due to the imbalance of the acid-amine ratio.
[0069] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing anti-fouling self-cleaning elastic nylon, characterized in that: The method comprises the following steps: randomly copolymerizing a soft segment monomer and a hard segment monomer to obtain anti-fouling self-cleaning elastic nylon; the raw materials of the soft segment monomer are a diamine containing a carbon fluorine structure and an alkane dibasic acid, or a dibasic acid containing a carbon fluorine structure and an alkane diamine; the structural formula of the diamine containing a carbon fluorine structure is: or , wherein n is an integer of 6 to 20; the structural formula of the dibasic acid containing a carbon fluorine structure is: or , where n is an integer from 6 to 20; The raw materials of the hard segment monomer are lactam, or alkane dibasic acid and alkane diamine; x:y is the mass ratio of the hard segment monomer to the soft segment monomer in the anti-fouling self-cleaning elastic nylon, x:y=0.5~0.65:0.35~0.5, x+y=1.
2. The method for preparing the anti-fouling self-cleaning elastic nylon according to claim 1, characterized in that: The lactam is at least one of caprolactam, decanolactam, undecanolactam and laurolactam.
3. The method for preparing the anti-fouling self-cleaning elastic nylon according to claim 2, characterized in that: The lactam is caprolactam or laurolactam.
4. The method for preparing the anti-fouling self-cleaning elastic nylon according to any one of claims 1-2, characterized in that: The alkane dicarboxylic acid is one of adipic acid, glutaric acid and sebacic acid; the alkane diamine is one of hexamethylenediamine, pentamethylenediamine and decanediamine.
5. The method for preparing the anti-fouling self-cleaning elastic nylon according to claim 1, characterized in that: The method specifically comprises the following steps: mixing the raw materials of the soft segment monomer and the hard segment monomer to ensure that the acid-amine molar ratio is 1:1-1.1, adding a catalyst and desalted water to carry out a salt-forming reaction, and then sequentially carrying out a prepolymerization reaction and a polymerization reaction to obtain anti-fouling self-cleaning elastic nylon.
6. The method for preparing the anti-fouling self-cleaning elastic nylon according to claim 5, characterized in that: The salt-forming reaction is as follows: salt-forming at 60-80° C. under normal pressure for 1-2 h.
7. The method for preparing the anti-fouling self-cleaning elastic nylon according to claim 5 or 6, characterized in that: The prepolymerization reaction is: prepolymerization at 220-260° C. for 1-2 hours, and a reaction pressure of 1.0-2.0 MPa.
8. The method for preparing the anti-fouling self-cleaning elastic nylon according to claim 5 or 6, characterized in that: The polymerization reaction is as follows: slowly draining water and releasing the pressure to normal pressure at 220-260° C. for 0.5-2 hours, and evacuating to -0.01-0.1 MPa for 0.5-3 hours.
9. An anti-fouling self-cleaning elastic nylon prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Antibacterial and soil-release finishing process of nylon fabric
CN110952304A
Fluorinated polyamide and preparation method thereof
CN110358038A
Material for making toothbrush bristle and its preparation method
CN1903912A